The Role of Water Law in the Sustainable Development in Indonesia - Pulung Widhi Hari Hananto (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
Air selalu menjadi bagian dari kehidupan manusia dan sangat penting untuk kebutuhan manusia. Dalam beberapa dekade terakhir, polemik air telah meningkat dan membuat banyak korban dengan beragam latar belakang. Masalah utama tidak ada manajemen air dan keamanan air yang efektif (perlindungan air). Karena itu, kurangnya akses ke air bersih selalu terjadi dan yang terburuk, juga memberikan dampak serius dalam aspek hak asasi manusia dan hambatan besar bagi pembangunan berkelanjutan. Karena itulah diperlukan peran hukum air untuk menyelesaikan masalah ini. Dalam makalah ini, penulis ingin menguraikan dan menyelaraskan peran pentingnya hukum air untuk menjamin pembangunan berkelanjutan. Abstract Water always have been a part of human’s life and it is very essential for human’s need. In recent decades, the polemic of water has increased and made of lot victim with diverse background. The major issue there’s no effective water management and water security (water protection). Because of that, the lack of access to clean water always happen and the worst, also gives serious impact in human right aspect and big obstacle for sustainable development. That’s why it needs a role of water law to resolve this problem. In this paper, the writer would like to elaborate and harmonize the importance role of water law in order to guarantee the sustainable development.